THE ONTOLOGY OF ARABIC CURRICULUM AT PESANTREN ATTAHDZIB JOMBANG - Nurcholis, Ahmad; Sirad, Mochamad Chobir; Harianto, Budi; Hidayatullah, Syaikhu Ihsan (Arabi : Journal of Arabic Studies, 2020)
Some pesantrens have accommodated the madrasah or formal school education programs, both the curriculum and the learning methods. One of them is pesantren Attahdzib. This article aimed to describe, analyze, and interpret the ontology of Attahdzib Islamic boarding school curriculum, the process of implementing the curriculum, and the problems of its implementation. It was a qualitative research with descriptive analysis. The results showed that the the curriculum was implemented through some methods such as sorogan, bandongan or wetonan, and memorization. There were 2 types of education systems established in pesantren Attahdzib, namely diniyah education, and formal education. The problems faced in the implementation of curriculum were some teachers' disciplinary problem, the learning evaluation that sometimes considered hard and burden on students, and the formal schools' extra-activities that sometimes obstructed the pesantren's teaching and learning process.